Conocimiento y aplicación de las normas de bioseguridad en los estudiantes de clínica de la universidad Antonio Nariño sede Cúcuta (2023)
Compliance with biosafety standards allows reducing the risk of contamination from viral and infectious diseases, both for dental personnel and for the patient.